Demographic Angst : Cultural Narratives and American Films of the 1950s - Nadel, Alan, 1947- (Book collections on Project MUSE., 2018)
Prolific literature, both popular and scholarly, depicts America in the period of the High Cold War as being obsessed with normality, implicitly figuring the postwar period as a return to the way of life that had been put on hold, first by the Great Depression and then by Pearl Harbor. Demographic Angst argues that mandated normativity-as a political agenda and a social ethic-precluded explicit expression of the anxiety produced by America's radically reconfigured postwar population. Alan Nadel explores influential non-fiction books, magazine articles, and public documents in conjunction with films such as Singin' in the Rain, On the Waterfront, Sunset Boulevard, and Sayonara, to examine how these films worked through fresh anxieties that emerged during the 1950s.